2003
DOI: 10.1097/01.blo.0000092986.12414.b5
|View full text |Cite
|
Sign up to set email alerts
|

Conventry Award Paper: Multicenter Determination of In Vivo Kinematics After Total Knee Arthroplasty

Abstract: A summation analysis of more than 70 individual kinematic studies involving normal knees and 33 different designs of total knee arthroplasty (TKA) was done with the objective of analyzing implant design variables that affect knee kinematics. Eight hundred eleven knees (733 subjects) were analyzed either during the stance phase of gait or a deep knee bend maneuver while under fluoroscopic surveillance. Fluoroscopic videotapes then were downloaded onto a workstation computer and anteroposterior (AP) femorotibial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
274
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 405 publications
(301 citation statements)
references
References 29 publications
21
274
1
5
Order By: Relevance
“…In this study, we found that knees with greater than 15°of normal axial rotation obtain deeper flexion than those with more than 3°of reverse rotation. It has been hypothesized that this reverse rotation pattern may limit TKA flexion as a result of the anteriorization of the lateral condyle [3]. Additionally, we found that knees with an ending normal axial rotation of greater than 3°obtained deeper flexion than those knees that had less normal-ending axial rotation or reverse-ending axial rotation.…”
Section: Discussionsupporting
confidence: 49%
“…In this study, we found that knees with greater than 15°of normal axial rotation obtain deeper flexion than those with more than 3°of reverse rotation. It has been hypothesized that this reverse rotation pattern may limit TKA flexion as a result of the anteriorization of the lateral condyle [3]. Additionally, we found that knees with an ending normal axial rotation of greater than 3°obtained deeper flexion than those knees that had less normal-ending axial rotation or reverse-ending axial rotation.…”
Section: Discussionsupporting
confidence: 49%
“…Numerous kinematic analyses of the normal knee have documented greater mean posterior motion of the lateral condyle relative to the medial condyle, leading to a mean internal rotation of the tibia with progressive knee flexion [9,15,23,25,27,29]. Komistek et al reported the lateral condyle achieved more posterior motion than the medial condyle, 19.2 mm and 3.4 mm, respectively, with increasing knee flexion during a deep knee bend [25].…”
Section: Discussionmentioning
confidence: 99%
“…With increasing knee flexion, the normal knee reportedly experiences more posterior motion of the lateral condyle leading to internal rotation of the tibia with respect to the femur [18,22,25]. In contrast to the normal knee, in vivo kinematic analyses suggest subjects undergoing TKA often experience a motion pattern opposite the normal knee where the condyles slide in the anterior direction with increasing knee flexion [2,8,9,24,28,31,[34][35][36][37]. Also, in vivo kinematic studies involving patients undergoing TKA have documented reverse rotational patterns [2,10] and lateral condylar liftoff [13,21,34,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters should include early failure rates, patient reported outcomes, radiographic findings, and ultimately long-term survival and revision rates. These parameters are a part of any long-term registry with level three and four data already established in many advanced countries and gaining momentum in the United States through the American Joint Replacement Registry [2,4].…”
Section: Where Do We Need To Go?mentioning
confidence: 99%